Impacts of the CPTPP on the Improvement of Vietnam’s Intellectual Property Law - Que Anh, Nguyen Thi; Thao, Nguyen Bich (VNU Journal of Science: Legal Studies; Vol 35 No 3, 2019)
The Intellectual Property Chapter in the Comprehensive and Progressive Agreement for Trans-Pacific Partnership imposes many new obligations on Vietnam, which requires an overhaul of Vietnam’s intellectual property law in order to implement the IP provisions in this Agreement. This article anaylyzes the IP provisions in CPTPP, compares with the current Vietnamese law and with the newly amended Law on Intellectual Property, which was adopted by the National Assembly on June 14, 2019, then identifies which provisions have met the requirements of CPTPP and which provisions need further amendment and supplement.